A history of the world's religions - Noss, David S. (Macmillan College Pub., 1990)
A textbook for introductory college courses in the history of religions, published since 1949 as Man's religions. Surveys the origins, development, and divisions of the major religions of India, the Orient, and the Middle East. Each chapter includes a glossary, most with pronunciation indicated.